Paper-based nanosensors to evaluate community-wide illicit drug use for wastewater-based epidemiology - Mao, Kang; Yang, Zhugen; Zhang, Hua; Li, Xiqing; Cooper, Jonathan M. (Elsevier, 2020)
Wastewater-based epidemiology (WBE) is a powerful technique for monitoring illicit drugs of abuse in the community. Here, we report on a surface-enhanced Raman scattering/spectroscopy (SERS) sensor for the sensitive and selective detection of methamphetamine based on the assembly of noble metal core-shell nanoparticles on a bespoke glassy nanofibrous electrospun paper matrix. The hierarchical structure of the fibrous paper, modified with the synthesized Au@Ag core-shell nanoparticles (Au@Ag) possessing good SERS efficiency, enables us to evaluate the community-wide prevalence of methamphetamine in wastewater treatment plants around Beijing. We show that when normalized for the daily flow of the wastewater treatment plants, higher mass loads of drugs are found in sewage influent from urban areas, implying greater local methamphetamine usage than that in less populated areas. These user-friendly and disposable paper devices demonstrate the applicability of rapid on-site illicit drug detection, illustrating the application to wastewater-based epidemiology, which has the potential to inform government agencies regarding societal interventions.
Keywords: Wastewater-based epidemiology; SERS; Nanosensors; Illicit drugs; Illicit drugs